Prevention and treatment of white spot lesions in orthodontic patients - Maryam Khoroushi; Marzie Kachuie (Wolters Kluwer Medknow Publications, 2017)
Decalcification of enamel, appearing as white spot lesions (WSLs), around fixed orthodontic appliances is a major challenge during and after fixed orthodontic treatment by considering the fact that the goal of orthodontic treatment is to enhance facial and dental esthetic appearance. Banded or bonded teeth exhibit a significantly higher rate of WSLs compared to the controls with no braces as fixed appliances and the bonding materials promote retention of biofilms. These lesions are managed in the first step by establishing good oral hygiene habits and prophylaxis with topical fluorides, including high-fluoride toothpastes, fluoride mouthwashes, gels, varnishes, fluoride-containing bonding materials, and elastic ligatures. Recently, other materials and methods have been recommended, including the application of casein phosphopeptides-amorphous calcium phosphate, antiseptics, probiotics, polyols, sealants, laser, tooth bleaching agents, resin infiltration, and microabrasion. This article reviews the currently used methods to manage enamel demineralization during and after orthodontic treatment and the risk factors and preventive measures based on the latest evidence.